HASIL BELAJAR RANAH SIKAP MODEL TEAM GAME TOURNAMENT, JIGSAW, DAN GROUP INVESTIGATION PENDIDIKAN KEWARGANEGARAAN - Enyang Suandi; Pargito Pargito; Eddy Purnomo (Jurnal Studi Sosial / Journal of Social Studies, 2013)
Abstract, the purpose of the research is to analysize learning result that teaching uses Team Game Tournament, Jigsaw and Ggroup Investigation, on the presents positive attitude to law system and national judge. This research include comparative with experiment approaching. Experiment is done for 6 class (12 x 45 minutes) begins October 5 until December 15, 2013, on three different methodes, X1 use TGT, X3 use Jigsaw, and X5 use GI. Based on analysis, conclude that attitude to national law and court system, there is a different attitude to national law and court system for students using TGT, Jigsaw and GI model in learning. The students’ attitude to national law and court system which using TGT is more positive than Jigsaw. Students’ attitude to national law and court system which using TGT is more positive than GI. The students’ attitude to national law and court system which using Jigsaw is more positive than GI.Keywords:  TGT,  jigsaw, GI, learning result.